Analysis Strategy of Building Utilization Optimizing in Public Works Training Center Region IV Surabaya - Kurniawan, Heru; Artama Wiguna, I Putu; Indryani, Retno (IPTEK Journal of Proceedings Series, 2017)
Public Works Education and Training Center in Region IV of Surabaya is one of work units from education and training center, ministry of public work. It has a role as the organizer of any educational and training as the administrator of non-taxable revenue. Public Works Education and Training Center in Region IV of Surabaya has building which can be used by the internal institute or by the public through the non-taxable revenue fee. However, the property itself is not sufficient compare to the activities held. It caused the utilization of the building is not optimal. The aim of this research is to analyze the strategy of improving the utilization of public work education and training center building area IV Surabaya. The method used in deciding the strategy was by analyzing the internal and external factors through SWOT method. The analysis process of the internal and external factors was done by using the Focus Group Discussion (FGD) method; they were determining the internal and external factors, evaluating them, and developing strategy. The FGD was attended by the internal authorities. By using the Grand Strategy Matrix would be gained the grand strategy of improving the utilization of the building, which then the derivative strategy was analyzed based on the highest score in EFI and EFE matrix. The result is the organization position in the big strategy matrix was in the first quadrant which encourages the aggressive growth. The grand strategies which believed suitable to the organization condition were the market development, market penetration, and product improvement.